The crystal structure of bis(4-(6-carboxy-8-ethyl-3-fluoro-5-oxo-5,8-dihydro-1,8-naphthyridin-2- yl)piperazin-1-ium) adipate tetrahydrate, C36H52F2N8O14 - Jiang Cheng-Jun; Xia Ying-Fan (Zeitschrift für Kristallographie - New Crystal Structures, 2022)
C36H52F2N8O14, triclinic, P1‾$\overline{1}$ (no. 2), a = 6.9775(4) Å, b = 9.0785(6) Å, c = 16.8942(10) Å, β = 92.778(2)°, V = 990.91(11) Å3, Z = 1, Rgt(F) = 0.0397, wRref(F2) = 0.1088, T = 170 K.